2020
DOI: 10.1080/07315724.2020.1737984
|View full text |Cite
|
Sign up to set email alerts
|

Altered Maternal Plasma Fatty Acid Composition by Alcohol Consumption and Smoking during Pregnancy and Associations with Fetal Alcohol Spectrum Disorders

Abstract: Objective: Polyunsaturated fatty acids are vital for optimal fetal neuronal development. The relationship between maternal alcohol consumption and smoking with third trimester plasma fatty acids were examined and their association with Fetal Alcohol Spectrum Disorders (FASD). Methods: Moderate to heavy alcohol-using and low/unexposed comparison women were recruited during mid-pregnancy from two prenatal clinics in Ukraine. The participants' infants underwent physical and neurobehavioral exams prior to one-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…In particular, smoking predicted a reduction of around 40 µmol/L of DHA. These results confirm recent findings in the omega-3 index in erythrocyte or in total n-3 in serum fatty acid [12][13][14][15]17,53]. This influence is possibly caused by the adverse effect of smoking on the conversion process of ALA to DHA [54,55].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, smoking predicted a reduction of around 40 µmol/L of DHA. These results confirm recent findings in the omega-3 index in erythrocyte or in total n-3 in serum fatty acid [12][13][14][15]17,53]. This influence is possibly caused by the adverse effect of smoking on the conversion process of ALA to DHA [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding another unhealthy lifestyle habit, some studies have found that maternal alcohol consumption has been associated with worse n-6 and n-3 FA concentrations [12,15,16,18,53] since it could impair lipid metabolism [59]. However, our results did not find any significant association, probably due to the fact that the amount of alcohol consumption in our sample is low (3.01 g/day ± 15.2) in comparison to women who consume alcohol frequently [16] or moderately-heavily [53].…”
Section: Discussionmentioning
confidence: 99%
“…We also found an increase in palmitic and arachidonic acids in PE in PAE mice (Figure 2A). Of note, previous studies showed an increase of arachidonic acids in maternal plasma from mothers who consumed alcohol during pregnancy and had children with lower cognitive test scores compared to those mothers who consumed alcohol but had children with the normal scores (Sowell et al, 2020). In the same study, palmitic acids in maternal plasma were also positively correlated with alcohol intake.…”
Section: Discussionmentioning
confidence: 93%
“…Alcohol interacts directly with fatty acid to produce fatty acid ethyl ester, thereby identified as a biomarker of maternal alcohol drinking (Himes et al, 2015). Furthermore, in pregnant mothers who drink alcohol, fatty acid composition in their plasma was different between mothers with offspring showing abnormal development and those showing normal development (Sowell et al, 2020). In animals exposed to alcohol throughout gestation, docosahexaenoic acid (DHA), an n-3 fatty acid, was reduced in phospholipid collected from the postnatal hippocampus (Kim, 2008; Wen & Kim, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few reports identifying nutrient intake of First Nations women at various stages of reproductive phases, at the present time, there are no reports identifying intakes for pregnant women at-risk either at the community, provincial, or federal level. A small number of international reports, which examine various dietary components with at-risk sub-analysis, have similarly smaller sample sizes ranging from 10 to 33 individuals in the at-risk group [ 53 , 54 ]. Therefore, this study provides the expected prevalence—a crucial variable in the calculation of the sample size for cross sectional designs.…”
Section: Discussionmentioning
confidence: 99%